Microiontophoresis and Micromanipulation for Intravital Fluorescence Imaging of the Microcirculation - Bagher, Pooneh (MyJove Corporation, 2011)
Microiontophoresis entails passage of current through a micropipette tip to deliver a solute at a designated site within an experimental preparation. Microiontophoresis can simulate synaptic transmission(1) by delivering neurotransmitters and neuropeptides onto neurons reproducibly(2). Negligible volume (fluid) displacement avoids mechanical disturbance to the experimental preparation. Adapting these techniques to the microcirculation(3) has enabled mechanisms of vasodilation and vasoconstriction to be studied at the microscopic level in vivo(4,5). A key advantage of such localized delivery is enabling vasomotor responses to be studied at defined sites within a microvascular network without evoking systemic or reflexive changes in blood pressure and tissue blood flow, thereby revealing intrinsic properties of microvessels. A limitation of microiontophoresis is that the precise concentration of agent delivered to the site of interest is difficult to ascertain(6). Nevertheless, its release from the micropipette tip is proportional to the intensity and duration of the ejection current(2,7), such that reproducible stimulus-response relationships can be readily determined under defined experimental conditions (described below). Additional factors affecting microiontophoretic delivery include solute concentration and its ionization in solution. The internal diameter of the micropipette tip should be ˜ 1 μm or less to minimize diffusional 'leak', which can be counteracted with a retaining current. Thus an outward (positive) current is used to eject a cation and a negative current used to retain it within the micropipette. Fabrication of micropipettes is facilitated with sophisticated electronic pullers(8). Micropipettes are pulled from glass capillary tubes containing a filament that 'wicks' solution into the tip of the micropipette when filled from the back end ("backfilled"). This is done by inserting a microcapillary tube connected to a syringe containing the solution of interest and ejecting the solution into the lumen of the micropipette. Micromanipulators enable desired placement of micropipettes within the experimental preparation. Micromanipulators mounted on a movable base can be positioned around the preparation according to the topography of microvascular networks (developed below). The present protocol demonstrates microiontophoresis of acetylcholine (ACh(+) Cl(-)) onto an arteriole of the mouse cremaster muscle preparation (See associated protocol: JoVE ID#2874) to produce endothelium-dependent vasodilation. Stimulus delivery is synchronized with digitized image acquisition using an electronic trigger. The use of Cx40(BAC)-GCaMP2 transgenic mice(9) enables visualization of intracellular calcium responses underlying vasodilation in arteriolar endothelial cells in the living microcirculation.